2020
DOI: 10.1177/1545968320948610
|View full text |Cite
|
Sign up to set email alerts
|

Low-Frequency Repetitive Transcranial Magnetic Stimulation Over Contralesional Motor Cortex for Motor Recovery in Subacute Ischemic Stroke: A Randomized Sham-Controlled Trial

Abstract: Background Low-frequency repetitive transcranial magnetic stimulation (rTMS) over the contralesional motor cortex (M1) has demonstrated beneficial effects on motor recovery, but evidence among patients with subacute stroke is lacking. We aimed to investigate whether 1-Hz rTMS over the contralesional M1 versus sham rTMS could improve arm function in patients with subacute ischemic stroke when combined with rehabilitative motor training. Methods In total, 77 patients who were within 90 days after their first-eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 57 publications
2
39
0
Order By: Relevance
“…Eleven studies included a sham-control condition either in a crossover or parallel-group design (16,20,(33)(34)(35)(37)(38)(39)(40)(41)(42). Of the 11 shamcontrolled trials, only four were randomized, double-blind trials (19,20,35,38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies included a sham-control condition either in a crossover or parallel-group design (16,20,(33)(34)(35)(37)(38)(39)(40)(41)(42). Of the 11 shamcontrolled trials, only four were randomized, double-blind trials (19,20,35,38).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of rTMS protocols, 10 studies used excitatory rTMS (17,21,22,33,34,36,39) or iTBS (18,37,38) targeting ipsilesional M1 (17,18,21,22,34,(36)(37)(38)(39) or ipsilesional S1 (33), with either a single session (18,33,34,36,37,39) or a total of 10 sessions (17,21,22,38) of intervention. A total of 13 studies used inhibitory rTMS over contralesional M1, with a range from 5 up to 30 intervention sessions (19,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)41). Two studies used both inhibitory contralesional, as well as excitatory ipsilesional rTMS over M1 (35,40), and a single study measured the effects of a single session of excitatory contralesional rTMS on M1, dorsal premotor cortex (dPMC), and anterior intraparietal sulcus (aIPS) (16).…”
Section: Resultsmentioning
confidence: 99%
“…The site of location (i.e., cortical or subcortical) could also influence the treatment effects of rTMS. A recent study by Kim et al revealed that low-frequency rTMS applied to the contralesional hemisphere resulted in improvements in BBT and hand motor control only in the group without cortical involvement [ 54 ]. There are several potential explanations.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is promise for rTMS and TBS to improve stroke recovery (Zhang et al, 2017), there are also a number of negative reports from gold-standard randomized control trials (RCTs) (Dionísio et al, 2018;Kim et al, 2020). Several factors likely contribute to this disparity.…”
Section: Repetitive Stimulation Transcranial Magnetic Stimulation (Tms)mentioning
confidence: 99%